Inversion induced by temperature bacteriophage mu-1 in the chromosome of Escherichia coli K-12. - Faelen, M (1980)
Induction of the Mu prophage of a lysogenic HfrP4X strongly stimulates the early transfer of the purE gene, which is located far from the origin of transfer. By using a rec- Mu cts62 X lysogenic donor, it was established that this process reflects the inversion of the origin of transfer in part of the Hfr population. Hfr's with inverted polarity of gene transfer were isolated; their analysis suggests that two Mu genomes in opposite orientation surround the inverted DNA fragment. Due to the presence of the Mu genome of the invertible G segment, homologous regions in the same orientation can appear in Mu genomes in opposite orientation. In a Rec+ background, Hfr's with inverted polarity (i) return to their original polarity of transfer by recomination between the two inverted Mu and (ii) produce new F' strains by recombination between the two similarly oriented G segments.